Time Synchronization under Temperature and Distance Variations - Susin, Matheus Martins; Wanner, Lucas Francisco; Resner, Davi; Fröhlich, Antônio Augusto (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2017)
The Trustful Space-Time Protocol (TSTP) allows for time synchronization to be performed upon receiving any message from another node in a sensor network, removing the need for explicit synchronization messages. Previous work has shown that TSTP performs well under controlled experimental environments. In this work, we analyze how the quality of synchronization in TSTP is affected when nodes are communicating over varying distances, and across a temperature gradient. The results show that, while distance and packet loss has only a small effect on the quality of the synchronization, high temperatures of 80°C and up can negatively affect it. The results from the temperature variation experiments are incorporated into a network simulator to make its clock drift model more realistic, as well as tied to current node temperature.